The Wage Effects of Regional Brain Gain and Brain Drain Revisited - Joachim Möller; Johann Eppelsheimer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Since the study by Moretti (2004) for the US, it is widely accepted that the spatial distribution of human capital plays an increasing role for regional labor market outcomes. Like in the pioneer approach we assume that workers' productivity at the firm level depend on the regional share of the high skilled. We extent the theoretical framework, however, by decomposing the change in the regional share of high-skilled workers into brain drain, brain gain as well as into labor market entry and exit effects. This allows us to investigate hypotheses about the extent and nature of knowledge spillovers in more detail. For the empirical part we analyze a large administrative panel data set. Including a series of controls as well as fixed effects for the worker, occupation, industry, region and year we find a significant negative relationship between brain drain and the regional wage level of low- and high skilled workers and a positive one for brain gain. These results are robust across different specifications and hold for Germany as a whole and West Germany alone. If estimated separately, we find much weaker and partly statistically not significant knowledge spillovers for East German regions. In general, brain drain and brain gain effects are of similar order of magnitude, whereas the effect of labor market exits of high-skilled workers exceeds that of labor market entries in absolute value. Using instrumental variable methods we show that the basic results are not driven by endogeneity bias.
Keywords: J24; J31; O15; 330